A COMPARATIVE STUDY ON PRESERVATION OF ANIMAL SKIN USING GAMMA IRRADIATION AS AN ALTERNATIVE TO SALT CURING TECHNIQUE - Akawu, Patience I.; Onoja, Michael A.; Musa, Y.; Akawu, I.; Akintade, S. A.; Jakheng, W. E.; Aliyu, U. S. (FUDMA Journal of Sciences, 2023)
The study on investigation of the physico-mechanical properties of hide/skin (Sokoto red goat) using gamma ray irradiation as alternatives to salt curing preservation technique aims at converting flayed skin into the state of being resistant to putrefaction and it is accomplished by destroying active bacteria. The leather industry being one of the largest contributors to Nigeria’s economy requires more attention to be given to it. Despite its contribution to the economy of the nation, the methods of processing leather poses serious threat to the environment. The  Salt preservation, the conventional method of preserving skin is practiced by most tanners and it employs approximately 40-50% sodium chloride which is subsequently removed into the environment during soaking operation and this pollutes the environment. To overcome the limitation of such method, an eco-friendly method was introduced, which is the irradiation (Gamma ray) method which serves as a safer and ecofriendly alternative technique of preservation. The type of tanning method applied after preservation is the vegetable tanning method using the Divi-divi(Caesalpinia coriaria) pods which is also eco-friendly. From the research carried out, the leather preserved using gamma had 21.878 N/mm2 at 300Gy, 3.27 Kg/cm2 at 300Gy, 0.33mm at 350Gy, 75oC at 200Gy, and 0.537g/cm3 at 150Gy which are the highest values for tensile strength, resistance to compression, indentation index, shrinkage temperature, and apparent density respectively as compared to the salt cured samples which had 23.963 N/mm2, 4.50 Kg/cm2, 0.23 mm 72oC, and 0.515 g/cm3 values for tensile strength, resistance to compression, indentation index...
Keywords: Preservation; Animal Skin; Irradiation Technique; Leather